Hollywood en los relatos pulp de Robert Leslie Bellem = Hollywood in Robert Leslie Bellem’s pulp stories. - Gutiérrez, José Ismael (Estudios Humanísticos. Filología, 2018)
Todas las acciones de los cuentos sobre Dan Turner, escritos por Robert Leslie Bellem para las revistas pulp, transcurren en el contexto de la industria cinematográfica hollywoodense. Este artículo indaga en las diversas situaciones criminales y en los tipos de personajes que aparecen en esta serie detectivesca: estrellas de cine, dobles, productores, agentes, extras, una infinidad de glamurosas starlets…, de los que el narrador autodiegético (es decir, el detective protagonista) proyecta una imagen nada idealizada. This article examines some characteristics of the series about Dan Turner written Robert Leslie Bellem. In these short stories, crime, intrigue, detective investigation, sexual content and satire are mixed with a colorful and colloquial linguistic style. All their actions take place in the context of the Hollywood film industry (of which Bellem had personal knowledge). So this irreverent detective’s mysteries are also linked to the genre category which we call "Hollywood narrative", which emerges over the course of the silent film era. In this sense, the work researches the types of characters that appear in these short stories -film stars, stuntmen, producers, agents, extras, an endless array of glamorous female starlets…-, all of whom are depicted by an autodiegetic narrator (that is, the detective-protagonist) in a clearly non-idealized and funny fashion.